Environmental Law Aspect in Medical Hazardous and Toxic Waste Control - Adityaningrum, Narita (Riwayat: Educational Journal of History and Humanities, 2023)
Hazardous toxic waste (B3) medical waste in Indonesia is undeniably a serious threat that impacts environmental pollution as well as public health. Data from the Ministry of Environment and Forestry (KLHK) shows that the control of such waste by hospitals still does not meet the prescribed standards. Law No. 32 of 2009 concerning Environmental Protection and Control (PPHL) has regulated that every person who generates hazardous waste is obliged to manage the waste they produce and if they are unable to do so, they must hand over the control to another party. The problems in this article are, what are the obstacles faced by hospitals in the control of medical B3 waste and how is the solution to the problem of hospital medical B3 waste control. This article is a normative legal research, descriptive in nature, and deductive inference. The conclusion of this research is that the obstacles faced by hospitals in the control of medical hazardous waste are due to the lack of waste treatment facilities compared to the amount of medical hazardous waste generated by hospitals and solutions to medical waste control problems, among others, by adding medical hazardous waste control facilities and encouraging each hospital so that the hospital can self-manage the waste.